Why don't they do it? Handwashing barriers and influencer study in Faridabad district, India. (November 2021) - Gupta, V; Anand, S
Background: Handwashing has been widely accepted as the simplest protection against communicable diseases. However, despite proven effectiveness and cost-efficiency, adoption of regular handwashing is still poor in developing countries. As children in school-going age are vulnerable and continue to suffer from preventable illnesses, this study aims to spot barriers to handwashing among children while simultaneously recognizing the influencing factors to aid the solutions narrative for effective water, sanitation and hygiene (WASH) strategies. Methods: A school-based cross-sectional, mixed-method study was conducted in Ballabhgarh block, Faridabad district, India. A predesigned, pretested, structured questionnaire was administered to 106 class V students in five randomly selected rural government primary schools. Due permissions, consent and ethical clearances were taken. Results: The majority (>91%) of children were found to have low illness threat perception. The inability to visually see germs came out as one of the biggest barriers (46%) that were preventing children from practicing regular handwashing. Family, teachers and peers were found to be the most important sources of information for children and not any particular media channel. In fact, role of peers was found to be critical as 72% children said that they would wash hands if their friends were also washing hands. Conclusion: This study suggests children's need for visible proof of germs and associated casual attitude toward illness threat as a hitherto unexplored potential barrier to practicing regular handwashing. In addition, the human channel of communication seems to be the most relevant regarding public health messaging in rural heartlands. Despite 100% penetration of mobile phones and commonplace presence of television, it is the community ecosystem that is still the most trusted sources of information and influence. The unique role of peers found in this study could have strategic implications for future behaviour change interventions making a case for peer-to-peer behaviour modeling.